Advancing Obstructive Airway Disease Treatment: Dual PDE3/4 Inhibition as a Therapeutic Strategy - Rinzhin T. Sherpa; Cynthia J. Koziol-White; Reynold A. Panettieri (Cells)
Obstructive airway diseases, including asthma and chronic obstructive pulmonary disease (COPD), evoke significant global health concerns manifested by airway inflammation and obstruction. Despite their differing origins, shared pathophysiological features and responses to therapeutic interventions highlight common molecular mechanisms. Standard treatments include inhaled bronchodilators, with combination therapies offering enhanced symptom control. Cyclic AMP (cAMP) plays a crucial role in airway relaxation. Phosphodiesterase (PDE) decreases cAMP levels, thereby attenuating the relaxation of airway smooth muscle, making it a promising therapeutic target. The balance between cAMP production and degradation is essential for regulating airway tone and function. PDE inhibitors for the treatment of obstructive airway diseases have suffered challenges, with adverse side effects of prospective inhibitors causing clinical failures. Efforts to develop PDE inhibitors with an improved safety profile could prove to be beneficial as an add-on treatment for severe asthma and COPD. The recent FDA approval of Ensifentrine, a dual PDE3/4 inhibitor, can significantly advance COPD management by improving bronchodilation, reducing inflammation, and lowering exacerbation rates with favorable safety outcomes.